Caracterización y tipificación de fincas productoras de cacao (Theobroma cacao L.) Nacional y CCN51 en el Cantón Montalvo - Los Ríos, Ecuador - Ramos Arévalo, José Alfredo (2019)
This research project was executed through surveys of 180 producers; The constant questions of 67 questions addressed to the different producers of the Montalvo canton in order to know the characteristics of the producers and the problems that affect the field day by day, since we do not have updated information in recent years. The main objective of this research is the development and use of indicators and subindicators to characterize and typify cocoa-producing farms in various sectors of the Montalvo canton. The use of the indicators allows us to identify several shortcomings in ecological, economic and socio-cultural aspects. In the economic dimension, 31% of the surveyed producers have an average monthly net income of $ 300 to 400, it is also possible to specify that the productivity of cocoa in the property is very low. In the ecological or environmental dimension it is affected by the number of applications of agrochemicals in the crop, and it is also affected by factors causing losses in the diseases where the monilla predominates. In the sociocultural aspect we can observe 95% of the producers have basic services such as installation of water and electricity, while the level of education that predominates in the farmers is the complete and incomplete primary study and in the age of the farmers more than half have an age that is between 40 to 60 years